2011
DOI: 10.1021/am201151t
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Potassium Titanate Nanowires into Titanium Oxynitride Nanotubes

Abstract: Tunnel-structured potassium titanate with a K(3)Ti(8)O(17) phase was synthesized by direct oxidation of titanium powder mixed with KF(aq) in water vapor at 923 K. The reaction conditions were adjusted so that uniform single crystalline potassium titanate nanowires with [010] growth direction (length: 5-30 μm, diameter: 80-100 nm) were obtained. Nitridation of the nanowires by NH(3)(g) at 973-1073 K converted the titanate nanowires into rock-salt structured cubic phase single crystalline titanium oxynitride TiN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 27 publications
4
17
0
Order By: Relevance
“…[168] In case of TiONs, the presence of oxide phase aids in rapid surface redox reactions. [169][170][171][172] In the context of TiONs, This result is akin to the other TiN structures reported such as nanofibers (145 F g À 1 @2 mV s À 1 ) [173] and nanowires (123 F g À 1 @10 mV s À 1 ). By varying the O/N ratio, the properties of the oxynitride can be modified.…”
Section: Titanium Oxynitride (Tion)supporting
confidence: 67%
See 1 more Smart Citation
“…[168] In case of TiONs, the presence of oxide phase aids in rapid surface redox reactions. [169][170][171][172] In the context of TiONs, This result is akin to the other TiN structures reported such as nanofibers (145 F g À 1 @2 mV s À 1 ) [173] and nanowires (123 F g À 1 @10 mV s À 1 ). By varying the O/N ratio, the properties of the oxynitride can be modified.…”
Section: Titanium Oxynitride (Tion)supporting
confidence: 67%
“…By varying the O/N ratio, the properties of the oxynitride can be modified. [169][170][171][172] In the context of TiONs, This result is akin to the other TiN structures reported such as nanofibers (145 F g À 1 @2 mV s À 1 ) [173] and nanowires (123 F g À 1 @10 mV s À 1 ). [46] The performance of TiO x N y nanosheets attributes to porous morphology and divalent cations in nanosheets.…”
Section: Titanium Oxynitride (Tion)supporting
confidence: 67%
“…This proposition is in agreement with the reported results on the conversion of potassium titanate to Ti-oxynitrides. 33 A similar mechanism of formation of Ti-oxynitride can be expected in CT800, but with a higher reaction rate of nitridation, due to the increase in temperature to 800 C, resulting in an enhanced doping level of N in H-titanate to transform into a large amount of Ti-oxynitride as shown by the higher peak intensity of Ti-oxynitride in CT800 (Fig. 1).…”
Section: Discussionsupporting
confidence: 56%
“…The formation of TiO can be expected during high temperature nitridation of titanates, which is in close agreement with the recent report on the conversion of potassium titanate to TiO by heat treatment at 800 C in an NH 3 atmosphere. 33 In addition, Ti-oxynitrides were detected by XRD measurements of CT700 and CT800. It is suggested that the poorly crystallized structure of the H-titanate precursor provides excellent channels for the diffusion of N, and readily substitutes O and bonds to Ti atoms to form Ti-oxynitrides.…”
Section: Discussionmentioning
confidence: 99%
“…the nitridation stage, TiO 2 converts to titanium oxynitride, Ti(O,N) x (x  1) by substituting oxygen with nitrogen atoms: TiO 2 (s) + NH 3 (g)  Ti(O,N) x (s) + H 2 O(g). 34 Since the nitridation process is a nitrogen diffusion-controlled reaction 28,35,36 , the nitrogen content in Ti(O,N) nanoribbons can be controlled by varying the reaction parameters. Therefore, we set the same temperature of 800 °C for all nitridation reactions, but used different values of NH 3 (g) flow while systematically changing the reaction times (Table S1).…”
Section: Transformation To Titanium Oxynitride Nanoribbonsmentioning
confidence: 99%